Implications of anemia in patients undergoing PCI with Impella-support: insights from the PROTECT III study - Falah, Batla; Redfors, Björn; Zhao, Duzhi; Bharadwaj, Aditya S.; Basir, Mir Babar; Thompson, Julia B.; Patel, Rajan A. G.; Schonning, Michael J.; Abu-Much, Arsalan; Zhang, Yiran; Batchelor, Wayne B.; Grines, Cindy L.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background Anemia is prevalent among patients with cardiovascular disease and is associated with adverse outcomes. However, data regarding the impact of anemia in high-risk percutaneous coronary intervention (HRPCI) are limited. Objectives This study aimed to evaluate the impact of anemia in patients undergoing Impella-supported HRPCI in the PROTECT III study. Methods Patients undergoing Impella-supported HRPCI in the multicenter PROTECT III study were assessed for anemia based on baseline hemoglobin levels according to World Health Organization criteria. Patients were stratified into three groups, namely, no anemia, mild anemia, and moderate or severe anemia. Major adverse cardiovascular and cerebrovascular events (MACCE: all-cause death, myocardial infarction, stroke/transient ischemic attack, and repeat revascularization) at 30 and 90 days, and major bleeding events were compared across groups. Results Of 1,071 patients with baseline hemoglobin data, 37.9% had no anemia, 43.4% had mild anemia, and 18.7% had moderate or severe anemia. Anemic patients were older and more likely to have comorbidities. Anemia was associated with higher MACCE rates at 30 days (moderate to severe, 12.3%; mild, 9.8%; no anemia, 5.4%; p = 0.02) and at 90 days (moderate to severe, 18.7%; mild, 14.6%; none, 8.3%; p = 0.004). These differences persisted after adjustment for potential confounders at 30 and 90 days, and sensitivity analysis excluding dialysis showed similar results. Major bleeding at 30 days was also higher in anemic patients (5.5% vs. 1.2%, p = 0.002). Conclusion Baseline anemia in Impella-supported HRPCI is common and independently associated with MACCE and major bleeding, emphasizing its significance as a prognostic factor. Specific management strategies to reduce anemia-associated MACCE risk after HRPCI should be examined. Clinical Trial Information Trial Name: The Global cVAD Study (cVAD) ClinicalTrial.gov Identifier: NCT04136392 URL: https://clinicaltrials.gov/ct2/show/NCT04136392?term=cvad&draw=2&rank=2